Antitumor Activity of a 5-Hydroxy-1H-Pyrrol-2-(5H)-One-Based Synthetic Small Molecule In Vitro and In Vivo - Geng, Yunyun; Wang, Xiaojian; Yang, Luo; Sun, Haili; Wang, Yongqiang; Zhao, Yue; She, Ruiping; Wang, Mei-Xiang; Wang, De-Xian; Tang, Jun (PLOS ONE, 2015)
Alternative chemo-reagents are in great demand because chemotherapy resistance is one of the major challenges in current cancer treatment. 5-hydoxy-1H-pyrrol-2-(5H)-one is an important N-heterocyclic scaffold that is present in natural products and medicinal chemistry. However, its antitumor activity has not been systematically explored. In this study, we screened a panel of 5-hydoxy-1H-pyrrol-2-(5H)-one derivatives and identified compound 1d as possessing strong anti-proliferative activity in multiple cancer cell lines. Cell cycle analysis revealed that 1d can induce S-phase cell cycle arrest and that HCT116 was sensitive to 1d-induced apoptosis. Further analysis indicated that 1d preferentially induced DNA damage and p53 activation in HCT116 cells and that 1d-induced apoptosis is partly dependent on p53. Furthermore, we showed that 1d significantly suppressed tumor growth in xenograft tumor models in vivo. Taken together, our results suggest that 5-hydoxy-1H-pyrrol-2-(5H)-one derivatives bear potential antitumor activity and that 1d is an effective agent for cancer treatment.